Hipotermia terapêutica em pacientes com asfixia neonatal - Estudo transversal em UTI neonatal do Sul do Brasil - Mariana Martins Denicol; Marcelo de Freitas Calegari; Cátia Rejane Soares de Soares; Valéria Raymundo Fonteles Ritter (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: Neonatal asphyxia causes a large part of infant deaths, especially during the perinatal period. In addition to the high mortality rate, it is also responsible for the majority of brain disabilities in patients born at term. Therapeutic hypothermia is the therapy recognized for reducing brain damage in newborns who suffered asphyxia and progressed with moderate to severe encephalopathy. OBJECTIVE: The present study compares outcomes in patients undergoing therapeutic hypothermia in relation to patients who had criteria for initiating the protocol at birth, however, due to worsening of the condition or delay in starting therapy, they did not complete the 72 hours of therapy. METHODS: It is a Cross-sectional study carried out through analysis of the neonatal ICU database at Hospital da Criança Conceição from March 2017 to September 2020. RESULTS: This is a study with 21 patients sample, which 12 patients underwent therapeutic hypothermia and 9 did not perform or did not complete the therapeutic hypothermia protocol. The results showed better outcomes in the intervention group about the necessity of oxygen use and the possibility of oral feeding. CONCLUSION: The outcomes of this study demonstrate a tendency, already recognized by entities and units that use therapeutic hypothermia, with better outcomes in patients who underwent hypothermia.